Analisis Kepatuhan Koperasi Syariah Terhadap Prinsip Syariah Berdasarkan Permen K.Umkm Nomor: 35.3/Per/M.Kumkm/X/2007(Studi Kasus Di Bmt Akbar Dan Ksus An-Nur Kecamatan Tawangsari Tahun 2015) - Pamungkas Bayu, Bayu; , M. Muhtarom, SH, MH (2016)
According to the Statistics Agency Sukoharjo district, the percentage of the population in the district Tawangsari 99 percent. Of this amount, Tawangsari people in desperate need of systems based on Sharia, especially in the cooperative system. Cooperative sharia in Tawangsari which has the greatest asset and the greatest number of members and centered in the district Tawangsari is BMT Akbar and KSUS An-Nur. For the good of society against sharia cooperative services, the Ministry of Cooperatives and Small and Medium Enterprises (MSME) of the Republic of Indonesia, issued a policy on sharia cooperative health assessment guidelines set out in the Regulation of Minister No. 35.3 / Per / M.KUMKM / X / 2007, which is one aspect his assessment is about adherence to islamic principles of sharia cooperatives. The purpose of this research is to describe and determine the level of adherence to the principles of sharia sharia cooperative based candy K.UMKM number 35.3Per / M.KUMKM / X / 2007 Cooperative Syariah BMT Akbar and KSUS An-Nur in 2015. This research is eksplorasatoris sequential, ie a combination of qualitative approach with quantitative, with the method of interview, observation and documentation as methods of data collection in the field. While the method of data analysis used is a combination of exploratory sequential method, which begins with descriptive qualitative data analysis as a first stage, followed by the analysis of quantitative data on the basis of the results of the first phase for analysis by the level of compliance Islamic principles. Based on the research and analysis of data, it can be concluded that BMT Akbar and KSUS An-Nur in the category of Compliance to sharia principles based regulation minister K.UMKM number 35.3Per / M.KUMKM / X / 2007.